TOBAT DALAM PERSPEKTIF ALQURAN - Sadik, Moh. (Institut Agama Islam Negeri (IAIN) Palu, 2010)
This article deals with repent in the perspective of the Qurâan. The word taubah and the root words of it was found 85 times in the Qurâan with its derivations. Taubah means returning to God with obedience and commitment not to commit the offences forbidden by God. Taubah will be performed after a man or a woman has committed the offences and sins. In addition, taubah is performed as an obligation and medium to approach God as a realization of oneâs faith in God.